Entrance Skin Dose Measurement Using GafChromic Dosimetry Film for Adult Patients Undergoing Coronary Angiography (CA) and Percutaneous Transluminal Coronary Angioplasty (PTCA) - Endang Nurtriningsih; Kristina Tri Wigati; Erlin Ingrina; Yurneli Luthan; Supriyanto Ardjo Pawiro (Journal of Medical Physics and Biophysics, 2014)
The complexity of interventional procedures has led to increasingly longer procedure time that require significant fluoroscopic use. Fluoroscopy time is proportional to the patient dose. Once a threshold dose has been exceeded, the severity of the radiation effect at any point on the skin increases with increasing dose. The threshold dose for transient skin injuries is typically 2 Gy for erythema, the earliest detectable effect of radiation on the skin. Therefore, it is important to monitor radiation entrance exposure to the patients. Since it is not uncommon that a patient not only perform a single examination, the skin dose per examination is recommended to note if in the future radiation effect on the patient's skin arises. The skin dose records will help further treatment. The aim of this study is to evaluate patient dose in interventional radiology. Twenty one cardiac intervention procedures were studied: 12 coronary angiography (CA) dan 9 percutaneous transluminal coronary angioplasty (PTCA). The entrance surface dose were measure using DAP (dose-area product) and GafChromic XR-RV3 radiochromic film attached to the skin. GafChromic film measurement obtained the skin dose distribution on the back of the coronary area. In addition, we also measure the patient backscattering dose on the thyroid, gonad and eyes. Image analysis was performed using red channel component of standard RGB (red, green and blue) color space image. The correlation between maximum radiation surface dose and dose area product for two interventional procedures was investigated. We found a good correlation of DAP (dose-area product) and maximum entrance skin dose (R2 = 0.79, R2 = 0.52 for CA and R2 = 0.74 for PTCA). However, fluoroscopy time seems to have a poor relationship with the patient entrance surface dose (R2 = 0.43). The total irradiation time, DAP and entrance surface dose for PTCA procedures is higher than CA procedures because of the PTCA procedure is more complex. The entrance surface dose delivered to the patient can be easily measured when GafChromic films are used. The GafChromic dosimetry allows precise mapping of the skin dose distribution, when placed close to the skin. The GafChromic film results that the radiation dose to the surface for PTCA procedure greater than CA.